Effectiveness of virtual or augmented reality therapy in improving physical functionality in physical rehabilitation: a systematic review - Aishah, Iily Insyirah; Sazali, Razif; Md Yusoff, Yusandra; Zulqarnain, Muhammad; Haziq, Amrun; Adnan, Aizzat; Linoby, Adam (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This systematic review synthesizes evidence from trials involving virtual and augmented reality (VR/AR) in physiotherapy to address existing gaps in clinical mapping and functional outcome analysis. By aggregating data from four major databases up to January 2025, the study evaluates the impact of various devices, dosages, and task-oriented interventions across diverse clinical populations. The findings aim to clarify the variables associated with superior physical recovery, providing a comprehensive appraisal of how immersive technologies can optimize rehabilitation outcomes compared to traditional methods.